2017
DOI: 10.1111/cfs.12372
|View full text |Cite
|
Sign up to set email alerts
|

Accomplishing irony: Socializing foster children into peer culture

Abstract: Parents indirectly influence their children's peer interactions by implicit socialization and directly by interference. They influence their (young) children's doings by supervising their contacts with friends, monitoring where they go, and facilitating their meetings with friends at home. Adolescents' growing orientation to peers is often at the cost of direct contact with their parents. Potentially, conversations with adolescent children become significant moments for parents to collect information about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…A previous study on interaction between professional foster parents and adolescents in family homes, based on direct (video-) observation, showed that professional foster parents hardly ever intervene in adolescents' verbally ironic disputes and even gear their reactions towards preparing them for future disputes with other peers (van Nijnatten, Matarese, & Noordegraaf, 2017). This finding follows Kramer et al (1999) who found that passive parental non-intervention (parents leave it to the children but don't say so) is most common.…”
Section: Parental Responses To Conflictmentioning
confidence: 74%
“…A previous study on interaction between professional foster parents and adolescents in family homes, based on direct (video-) observation, showed that professional foster parents hardly ever intervene in adolescents' verbally ironic disputes and even gear their reactions towards preparing them for future disputes with other peers (van Nijnatten, Matarese, & Noordegraaf, 2017). This finding follows Kramer et al (1999) who found that passive parental non-intervention (parents leave it to the children but don't say so) is most common.…”
Section: Parental Responses To Conflictmentioning
confidence: 74%